Characterization of Plant Growth-Promoting Bacillus Isolates from the Rhizosphere of Tomatoes using Molecular and Functional Techniques: Characterization and Potential Applications of Plant Growth-Promoting Bacillus Isolates from Tomato Rhizosphere (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The rhizosphere, a critical environment that harbors a wide variety of microorganisms, is indispensable for facilitating plant development and maintaining soil quality. Bacillus genus members, referred to as Plant Growth Promoting Rhizobacteria (PGPR), possess the capacity to substantially enhance agricultural productivity and promote long-term sustainability. This study focuses on the methodology employed to isolate and characterize seven Bacillus PGPR (TRS-1-8) isolates that were identified in the rhizosphere of tomato plants. An assortment of characteristics that promote plant growth were evaluated in the PGPR strains solubility in zinc and phosphate, synthesis of phytotoxins and siderophores, chitinase production, hydrogen cyanide (HCN) and indoleacetic acid (IAA) synthesis, biofilm formation, and ACC deaminase activity. Furthermore, an assessment was conducted on their ability to impede the growth of pathogenic bacteria and fungi that have an adverse effect on plants. The identification of the Bacillus spp. in these isolates was achieved via genetic characterization utilizing 16S rRNA gene sequencing. In order to verify the genetic diversity of the isolates, BOX-PCR fingerprinting was an additional technique employed. The efficacy with which the isolates established colonies on tomato roots was observed. The results obtained from the greenhouse experiments demonstrated that the chosen isolates had a beneficial effect on a range of growth parameters pertaining to tomato plants. These parameters comprised shoot length, root length, and dried weight. The statistical analyses were conducted using GraphPad Prism, where the significance of the observed differences was emphasized. In summary, the Bacillus PGPR isolates obtained from the rhizosphere of the tomato plant demonstrate a wide range of growth-promoting attributes that make them highly beneficial for the implementation of sustainable agricultural methods. The study makes substantial advancements in the comprehension of the potential applications of these techniques in the fields of biofertilization and plant health management.